Employed and unemployed job seekers: Are they substitutes? - Simonetta Longhi; Mark Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2010)
The job search literature suggests that an increase in the proportion of job seekers who are employed reduces the probability of unemployed people finding a job. However, there is little evidence indicating that employed and unemployed job seekers have similar observed characteristics or that they apply for the same jobs. We use the British Labour Force Survey to compare employed and unemployed job seekers, and find differences in their individual characteristics, preferences over working hours, and job search strategies which do not vary with the business cycle. We conclude that unemployed people do not directly compete with employed job seekers.
Keywords: J29; J60; 330; on-the-job search; unemployment; job competition; Arbeitsmarkt; Arbeitsverhältnis; Arbeitslosigkeit; Arbeitsuche; Anspruchslohn; Wettbewerb; Großbritannien